The Concept of "Mental Accounting" as the Spirit of Personal Financial Management for Millennial Women - Uli Nuha, Sukma; Meilan, Ria; Qoni’ah, Alfinatul (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
The research objective seeks to examine the ethno-economic dimensions that encourage Millennial Women to form behavioral decisions in managing personal finances. The novelty in this research is describing and analyzing the concept of "Mental Accounting" in managing personal finances, thus creating financial independence for women in Indonesia and becoming a new color in accounting research. The ethno-economic method was chosen in the research with the aim of explaining the reality of the behavior of the millennial generation in managing personal finances. The results of the study found the meaning of the concept of "mental accounting" applied by Millennial Women in managing personal finances in accordance with the Ethno-Economic dimension, namely past financial expenditure, budgeting planning for future expenditure and financial behavioral decisions. The theoretical contribution to this research is to strengthen the concept of "Mental Accounting" and human capital theory. The practical contribution of this research can be used as a basis for forming a personal financial management model for millennial women in Indonesia.